Prosedur Kerja, Hubungan Antar Manusia, Kesejahteraan Kerja dan Disiplin Kerja terhadap Prestasi Kerja Pegawai Dinas Perdagangan Lahat - Titi Hasanah; Pahlan Pahlan; Markus Markus (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine the influence of work procedures, human relations, work welfare and work discipline both partially and simultaneously on the work performance of Lahat Trade Service employees. The research method used in this research is a quantitative method using questionnaires distributed to respondents. Test data quality using validity tests, reliability tests, normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial tests and coefficients of determination. Work procedures have a significant effect on the work performance of Lahat Trade Service employees. Human Relations Have a Significant Influence on the Work Performance of Lahat Trade Service Employees. Work Welfare Has a Significant Influence on the Work Performance of Lahat Trade Service Employees. Work Discipline Has a Significant Influence on the Work Performance of Lahat Trade Service Employees. Work Procedures, Human Relations, Work Welfare and Work Discipline Have a Significant Influence Together on the Work Performance of Lahat Trade Service Employees. Keywords: Work Discipline, Human Relations, Work Welfare, Work Performance, Work Procedures